Paracoccidioidomycosis: Latin America's own fungal disorder (2012)
Paracoccidioidomycosis (PCM) is a systemic, endemic fungal disorder restricted to Latin America (Mexico to Argentina); Brazil accounts for the largest number of cases. Imported cases diagnosed in North America, Europe and Asia represent patients who had previously lived in recognized endemic areas. Paracoccidioides brasiliensis, the etiologic agent, is a thermally dimorphic fungus that in patients and cultures at 37 C adopts a yeast form while at lower temperatures it behaves as a mold that bears the infectious conidia. PCM has a peculiar gender distribution with preference for adult males at a ratio of ?11 to 1. PCM afflicts predominantly adult males engaged in agriculture. It is mostly a chronic disease with acute/subacute cases accounting for less than 15 % of all reports. Specific diagnosis is established late and although available therapy is usually successful in controlling the fungal infection, patients who survive usually develop residual fibrotic lesions that heavily impair their quality of life. © 2012 Springer Science+Business Media New York.